PROSES ULTRAFILTRASI UNTUK PENJERNIHAN SARI BUAH MARKISA (Passiflora quadrangularis) DENGAN MEMANFAATKAN MEMBRAN KERAMIK - -, Refinel; Tetra, Olly Norita; Usmita, Roza Melia (Jurnal Riset Kimia, 2016)
Ultrafiltration of passion fruit juice using variation thickness of ceramic membrane has been done.Â  The result shows that aquades flux value in 25 minutes for membrane 1.5; 2.0; 2.5; 3.0; and 3.5 mm is 17.0135; 19.1947; 10.9061; 10.9061 and 4.3624 L/h m2. Whereas passion fruit juice in same time for membrane 1.5; 2.0; 2.5 mm is 8.2886; 5.6712 and 4.3624 L/h m2. For membrane 3.0 and 3.5 mm it has not been done because flux value are too small that indicate fouling. Physical and chemical properties parameter in ultrafiltration of passion fruit juice obtained for turbidity and color very different between passion fruit juice before and after ultrafiltration, whereas reducing sugar and vitamin C are not significant different between passion fruit juice before and after ultrafiltration. Determination rejection coefficient value of membrane for turbidity, color Â relatively significant whereas for reducing sugar and vitamin C are relatively not significant.